The genetic variation and genetics of the resistance of maize (Zea mays L.) to the western corn rootworm (Diabrotica virgifera virgifera LeConte). - Larsen, John S. (University of Ottawa (Canada), 1999)
This study examines the genetics and genetic variation of maize resistance to Diabrotica virgifera virgifera LeConte (rootworm). Rootworm resistance is a complex, multi-trait characteristic with inheritance mechanisms not fully understood or explained. In order to better understand the mechanisms of rootworm resistance and the genetic parameters that condition this trait, three studies were undertaken. The first study examined the genetic variation of components of resistance in twenty-three DEKALB Genetics Corporation hybrids. They were assessed for hydroxamic acid content under uniform greenhouse conditions and compared with field assessments over two growing seasons for resistance to the Western Corn Rootworm in terms of root pull resistance, root damage ratings and root lodging. Hydroxamic acid levels of all hybrids were found to be moderately low resulting in low antibiosis. It appears that rootworm resistance in these hybrids is achieved mainly through tolerance, not antibiosis. The study suggests an opportunity for improvement of resistance in commercial inbreds through selection for antibiosis and hydroxamic acid content. In the second study, the combining ability, additive and dominance effects and the heritability of several traits important to rootworm resistance in maize were determined. GCA and SCA effects were found to be significant in the inheritance of hydroxamate content, root weight and plant height. GCA effects were found to be significant in relation to low root damage ratings. Heritability in a narrow sense as determined by the midparent/offspring regression was found to be 0.34 for hydroxamate content, 0.26 for root damage ratings and 0.35 for plant height. Additive genetic effects were found to be significant in the inheritance of root damage ratings, both additive and dominance effects contribute to the inheritance of plant height and dominance effects were found to be most important in the expression of root weight. In the third study, two inbred lines were used to develop an F2 :F3 population to further investigate the genetic parameters governing some of the traits important to rootworm resistance. The inbred lines used were 93n445 (susceptible) and 118.31 (resistant). Dominance effects were found to be significant in the inheritance of plant height, additive effects were found to be significant in the inheritance of root size and additive and dominance effects were found to be significant in the inheritance of root damage ratings. Heritability in a narrow sense was found to be 54% for root size, 55% for root damage ratings, 84.7% for stalk circumference and 89% for plant height for the inbreds used in this study. (Abstract shortened by UMI.)
Keywords: Agriculture, Agronomy.